What makes teachers satisfied with their profession? - Daniel Capistrano; Ana Carolina Cirotto (Arizona State University, 2014)
This article presents an analysis of the level of job satisfaction declared by Brazilian teachers in lower secondary schools. The research was based on results of a comparative survey conducted in 24 countries. This study identifies school factors that are associated with teachers' job satisfaction and provides some reflections on the impact of the evidence found in the research considering the debate regarding teacher profession and educational policies in Brazil.